The use of psychoactive prescription drugs among DUI suspects. (1st October 2015) - Karjalainen, Karoliina; Haukka, Jari; Lintonen, Tomi; Joukamaa, Matti; Lillsunde, Pirjo
Highlights: The use of psychoactive prescription drugs among DUI suspects was examined. The use of psychoactive prescription drugs and DUI appeared to be strongly associated. Physicians should inform the patients about the impairing effects of this medication. Possible substance use problems should be screened while prescribing these drugs. Abstract: Background: The study seeks to increase understanding of the use of psychoactive prescription drugs among persons suspected of driving under the influence (DUI). We studied whether the use of prescribed psychoactive medication was associated with DUI, and examined the difference in the use of prescription drugs between DUI recidivists and those arrested only once. Methods: In this register-based study, persons suspected of DUI ( n  = 29 470) were drawn from the Register of DUI suspects, and an age- and gender-matched reference population ( n  = 30 043) was drawn from the Finnish general population. Data on prescription drug use was obtained by linkage to the National Prescription Register. The associations of DUI arrest and use of psychoactive prescription drugs in different DUI groups (findings for alcohol only, prescription drugs, prescription drugs and alcohol, illicit drugs) were estimated by using mixed-effect logistic regression. Results: The use of psychoactive prescription drugs and DUI appeared to be strongly associated, with DUI suspects significantly more likely to use psychoactive prescription drugs compared to the reference population. Gender differences existed, with the use of benzodiazepines being more common among female DUI suspects. Moreover, DUI recidivists were more likely to use psychoactive prescription drugs compared to those arrested only once. Conclusions: In addition to alcohol and/or illicit drug use, a significant proportion of DUI suspects were using psychoactive prescription drugs. When prescribing psychoactive medication, especially benzodiazepines, physicians are challenged to screen for possible substance use problems and also to monitor for patients' alcohol or illicit drug use while being medicated.